De novo mutations in EBF3 cause a neurodevelopmental syndrome - Sleven, H; Welsh, S; Yu, J; Churchill, M; Wright, C; Henderson, A; Horvath, R; Rankin, J; Vogt, J; Magee, A; McConnell, V; Green, A; et al. (Elsevier, 2016)
Early B cell factor 3 (EBF3) is an atypical transcription factor that is thought to influence the laminar formation of the cerebral cortex. Here, we report that de novo mutations in EBF3 cause a complex neurodevelopmental syndrome. The mutations were identified in two large-scale sequencing projects: the UK Deciphering Developmental Disorders (DDD) study and the Canadian Clinical Assessment of the Utility of Sequencing and Evaluation as a Service (CAUSES) study. The core phenotype includes moderate to severe intellectual disability, and many individuals exhibit cerebellar ataxia, subtle facial dysmorphism, strabismus, and vesicoureteric reflux, suggesting that EBF3 has a widespread developmental role. Pathogenic de novo variants identified in EBF3 include multiple loss-of-function and missense mutations. Structural modeling suggested that the missense mutations affect DNA binding. Functional analysis of mutant proteins with missense substitutions revealed reduced transcriptional activities and abilities to form heterodimers with wild-type EBF3. We conclude that EBF3, a transcription factor previously unknown to be associated with human disease, is important for brain and other organ development and warrants further investigation.